2022
DOI: 10.1055/s-0042-1759515
|View full text |Cite
|
Sign up to set email alerts
|

Ciliopathies: Genetic Counseling

Abstract: Joubert syndrome (JS) follows autosomal recessive inheritance, with rare X-linked recessive cases. The disease is genetically heterogeneous with neurological features associated with multiorgan involvement (e.g., retinal dystrophy, nephronophthisis, hepatic fibrosis, and polydactyly). The incidence of JS and related disorders is between 1/80,000 and 1/100,000 live births. Many causative genes have been identified, all encoding for proteins of the cilium or the centrosome, making the JS part of a group of disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…29 30 31 32 33 34 35 36 37 These intricated pathophysiology reflects how complex molecular mechanisms underlie different congenital brain anomalies associated with impaired neurodevelopment. 38 39 40 41 42 43 44 45 46 47 48 In fact, in recent years, next-generation sequencing technologies, including exome and mRNA sequencing studies, have been shown to be essential in dissecting the pathophysiology of a wide array of childhood disorders. 49 50 51 52 53 54 55 56 57 58 59 This led to a better understanding of the subcellular alterations underlying diseases, including several regulatory networks and genetic together with nongenetic factors.…”
Section: Discussionmentioning
confidence: 99%
“…29 30 31 32 33 34 35 36 37 These intricated pathophysiology reflects how complex molecular mechanisms underlie different congenital brain anomalies associated with impaired neurodevelopment. 38 39 40 41 42 43 44 45 46 47 48 In fact, in recent years, next-generation sequencing technologies, including exome and mRNA sequencing studies, have been shown to be essential in dissecting the pathophysiology of a wide array of childhood disorders. 49 50 51 52 53 54 55 56 57 58 59 This led to a better understanding of the subcellular alterations underlying diseases, including several regulatory networks and genetic together with nongenetic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Such disorders may include a variety of monogenic as well as polygenic/genetically complex and/or environmental conditions with expanding clinical differential diagnosis, molecular heterogeneity, and associated (underlying) disease mechanisms. 55 56 57 58 59 60 61 62 The molecular dissection of these conditions and the underlying factors are interesting examples to explain the frequent intricated multisystemic, metabolic, and neurological abnormalities associated with a wide array of (both rare and common) pediatric disorders and useful etiologically targeted treatments. 54 63 64 65 66 67 68…”
Section: Follow-upmentioning
confidence: 99%
“…12 13 14 15 16 17 18 19 20 This is observed in the context of advances brough by basic sciences in regard to the molecular understanding of many pediatric neurological conditions, both rare and ultra-rare, associated with either genetic and non-genetic etiologies. 21 22 23 24 25 26 27 28 29 30 31 Several pathomechanisms have been identified, allowing a better pediatric-patient care in terms of clinical diagnosis, prognosis, and treatment. 32 33 34 35 36 37 38 39 Pediatric developmental disorders can often result by the combination of environmental and genetic factors and their aberrant interplay may sometimes lead to disease expression and metabolic and neurological abnormalities as part of the clinical phenotype in some cases.…”
Section: Introductionmentioning
confidence: 99%